Tinjauan Yuridis Terhadap Perlindungan Hukum BagiKonsumen Transaksi Jual Beli Online (Studi Jual BeliOnline Di Bengkel Knalpot Burnout Exhaust) - Aldi Ferdiansyah; Eti Mul Erowati; Wiwin Mochtar Wiyono (Wijayakusuma Law Review, 2019)
To find out how the form of Juridical Review of Legal Protection for Consumers Online Buy and SellTransactions, and to explore various aspects of issues that have been formulated in the formulation ofproblems. To achieve these objectives the author uses a normative juridical approach. The researchspecifications used are descriptive research. The data method is presented in the form of descriptions whichare arranged systematically. The condition of e-commerce on the one hand brings benefits mainly due toefficiency, but on the other hand brings doubt especially to legal issues regarding legal certainty of ConsumerProtection and the validity of business transactions. as stipulated in Article 1 paragraph 1 of Act No. 8 of 1999concerning Consumer Protection which states that "Consumer protection is any effort that guarantees legalcertainty to provide protection to consumers", in transactions that typically use paperbased economy, but intransactions through electronic media it turned into a digital electronic economy the need for special handlingin the eyes of the law itself. Article 1320 of the Civil Code should be based on the legal force owned byconsumers in conducting transactions. In the Electronic Information and Transaction Law Article 5 paragraph1 and 2 which states that "Electronic Information and / or Electronic Documents and / or their printouts arevalid legal evidence. And rather than consumer rights to obtain legal protection and can be a good start forlegal certainty for consumers.